Web, E-Report Web-based E-Report Information System Design - Harliana, Putri; Perdana, Adidtya; Farhana, Nurul Ain (Politeknik Ganesha Medan, 2024)
The E-Report application information system is a system that can assist and facilitate users in creating performance reports for a company. In this study, a web-based e-report system was developed and designed for digital reporting by field employees at PT. In this study, a web-based e-report system was developed and designed for digital reporting by field employees at PT. Cipto Sarana Nusantara, which specifically operates in the gas pipeline installation sector. Previously, the company generated field worker performance reports through manual systems, in the form of hard copies or sent via chat applications. This led to poorly organized reports received by administrators. To address this issue, the author developed E-Report, a web-based application that aims to facilitate field workers and administrators in submitting and collecting reports. By utilizing this system, reporting performance significantly improves in terms of reporting speed, accuracy, and ease. By utilizing this system, reporting performance significantly improves in terms of reporting speed, accuracy, and ease. By utilizing this system, reporting performance significantly improves in terms of reporting speed, accuracy, and ease. Furthermore, this system enables the generation of daily, monthly, and yearly reports more efficiently and effectively.